Coverage of Environmental Issues in Local Newspaper: an Analysis on Two Dailies of Rangpur, Bangladesh - Rahmatullah, Md.; Prodhan, Md. Tabiur Rahman; Islam, Md. Nazrul; Hossain, Md. Sajjat (International Multidisciplinary Research Journal, 2021)
This study examines the coverage of environmental issues in the local newspapers of Rangpur, Bangladesh. The results are based on an analysis of the content of environmental coverage in two local daily newspapers (The Daily Juger Alo and the Daily Prothom Khobor). The result depicts that The Daily Juger Alo and the Daily Prothom Khobor published an average of 1.91 and 1.22 stories per day, respectively. The top focused issue of these newspapers was natural disaster. Almost all the 258 (89.27%) stories were published without deep investigations or in-depth analysis. However, based on the average daily coverage of environmental issues, the authors conclude that environmental journalism is a strong subfield in local newspapers of Rangpur, Bangladesh. Future studies need to consider a large number of samples.